2010
DOI: 10.1038/modpathol.2010.145
|View full text |Cite
|
Sign up to set email alerts
|

The FOXL2 C134W mutation is characteristic of adult granulosa cell tumors of the ovary

Abstract: Granulosa cell tumors of the ovary represent B5% of malignant ovarian cancers. It has recently been reported that 95-97% of adult granulosa cell tumors carry a unique somatic mutation in the FOXL2 gene. We undertook this study to verify the presence of the FOXL2 Cys134Trp mutation in two geographically independent cohorts of granulosa cell tumors and to examine the expression pattern of FOXL2 in these tumors. A total of 56 tumors with the histological diagnosis of adult granulosa cell tumor from two centers, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
181
4
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 205 publications
(194 citation statements)
references
References 39 publications
7
181
4
2
Order By: Relevance
“…Our findings differ from those reported recently by Jamieson et al, 16 who found that levels were similar in all cases and controls studied, irrespective of their adult or juvenile nature. In our series, both tumor types expressed higher levels of FOXL2 mRNA than normal ovaries, especially granulosa cell tumors.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings differ from those reported recently by Jamieson et al, 16 who found that levels were similar in all cases and controls studied, irrespective of their adult or juvenile nature. In our series, both tumor types expressed higher levels of FOXL2 mRNA than normal ovaries, especially granulosa cell tumors.…”
Section: Discussioncontrasting
confidence: 99%
“…10 Previous studies have shown that this mutation is specific for the adult type granulosa cell tumors and is present in up to 95-97% of these tumors. 10,16 Recently, mutant FOXL2 has been found to induce lower levels of apoptosis compared with wild-type FOXL2. 17 The purpose of this investigation was to find out whether FOXL2 mutation and expression levels have a role in the pathogenesis of juvenile and adult granulosa cell tumors as well as its potential value as a prognostic factor.…”
mentioning
confidence: 99%
“…7,29,37,38 The latter were verified to possess the c.402C-G (p.C134W) mutation in FOXL2 5 and the mutation frequency of 95% corresponds to other published GCT series. [2][3][4] All histological diagnoses were carefully reevaluated, 29 patient charts were reviewed to obtain clinical data and recurrences were updated as of September 2009.…”
Section: Materials and Methods Human Tissue Samplesmentioning
confidence: 60%
“…52 Accordingly, several previous studies utilizing human GCT tissue series (reviewed in Fuller and Chu 53 ) have focused on genes and factors involved in the normal granulosa cell function. 5,7,29,54 We now describe the expression patterns of the AMH-signaling pathway components in GCT in detail and show evidence for AMH being a growth inhibitor for GCT. Previously, AMHRII positivity and AMH responsiveness have been reported in ovarian cancers originating from the Müllerian duct derivatives.…”
Section: Discussionmentioning
confidence: 85%
“…[1][2][3][5][6][7] To date PubMed indexed reports cite a total of 290 adult-type granulosa cell tumors that have been tested for the FOXL2 mutation of which 267 (92%)…”
Section: Discussionmentioning
confidence: 99%